Right Hepatectomy Enlarged to Cuadrate Lobe for Polycystosis - Torterolo, Edgardo; Lyonnet, Alberto; Carriquiry, Luis; Pradines, Jorge (Cirugía del Uruguay, 1980)
Review of polycystic liver and report of one voluminous case treated by fenestration surgery, which subsequently recurred, accompanied by incapacitating hepatomegaly. Since externa} segments of classic left lo be were healthy, surgery consisted of hepatectomy enlarged to Segment IV.